Invisible Men: Unlocking Compassion and Understanding the Needs of Older Men Behind Bars - Louise Ridley; Kathryn E. Waldegrave (Social Sciences)
Men over 50 years of age are the fastest-growing population group in the prison system, leading to the prison service of England and Wales now becoming recognised as the largest provider of residential care for older men. Roughly one in five prisoners (18%) is over 50 years of age. This paper focuses on the impact on both staff and prisoners of developing an understanding of the needs and concerns of older prisoners during prison officer training. The authors approach the study of the older prison population from their respective disciplines—criminology and health. Both authors are aware of the necessity for custodial staff to be prepared and equipped to respond and manage a growing number of individuals who are vulnerable and appreciate the need for prison staff to be supported in this process, with an understanding of the complexities that come with housing large numbers of ageing men within a custodial setting. This article explores the provision of training for newly recruited prison officers and considers what good practice might look like.